Eficiência fotoquímica e qualidade pós-colheita da mangueira (Mangifera indica L.) cv. Ubá sob dois regimes hídricos e duas condições de luz - Silva, Leonardo Faria (2016)
This study evaluates the effects of irrigation and intensity of photosynthetically active radiation on photochemical parameters of 'Uba' mango tree leaves in two commercial orchards during four periods: I -Fruit growth, II –fruit ripening , III -After harvest and IV -After pruning the plants. We also analyzed the total soluble solids (TSS), the titratable acidity (TA), the ratio SST/AT, the weight and the fruit volume. In the first orchard, the treatments were characterized according to the water availability, as irrigated plants(IRR) and rainfed plants (RAI) conditions. The fruitswere harvested with the green peel (Gr), stored at 27 ± 3 °C and analyzed for seven days; themature harvestfruit (M) were analyzed in the same day of the harvest. Each day was considered a maturation stage (Gr1, Gr2, Gr3, Gr4, Gr5, Gr6, Gr7andM). In the otherorchard the treatments were characterized according to the incidence of the sunrise under the crop position: East Side plants (ES) and West Side plants (WS). The fruits of this orchard were harvested ripened and analyzed at the same day of theharvest. In plants conducted under two water regimes (IRR and RAI) the RC/CS0(reaction centers density assets by analyzed cross-section), dVG/dt0(rate of excitation energy transfer between reaction centers) and PITOTAL(total performance index) were the most representative photochemical parameters indicated by the principal component analysis (PCA).Damage caused by water stress were more evident in RAI plants especially during the period offruit ripening (period II) with decrease in RC/CS0. After fruit harvest (period III) RAI plants that were under water stress due to lack of rainning, recovered the efficiency producingnew reaction centers. The recovery in this period was significantly important to the point of RAI plants have RC/CS0statistically equal to the IRR plants, suggesting that drought stress occurred when the 'Uba' mango tree were withfruit in full ripening stage only. The period IV, regardless of the water system, was the period with the largest differences in photochemical performance and PITOTALwas lower than in all other analysis periods. There was a small decrease of PITOTALin RAI plants and was significantlygreater than on the IRR plants. In the second orchard, it was observed that the plants located on the West Side received at 11 am a sharp increase in radiation and temperature. Photoinhibitory damage were clearly observed, with a drop in the electron transport of photosystem II (PSII) to photosystem I (PSI) (ET0/TR0= ?E0) and with a marked decreasein the PSII performance index (PIABS). During the fruit ripening and after the pruning of plants, there was a decrease of PITOTALin both growing conditions. The WS plants were more susceptible to the PITOTALdecrease in the ES plants. The photoinhibition was more evident in WS plants and during the reproductive period. Thus, the fruit growth period, the lower values of the specific flow of energy captured and transported (TR0/RC and ET0/RC) while in fruit ripening period, besides the decrease in these parameters was also were observed fall of the quantum yield and electron transport efficiency after reducing the Quinone A (fE0and ?E0), flow reducers electrons (RE0/RC) and the efficiency of PSI (fR0) and sharp decrease ofPITOTAL. The fruit originated from WS plants wasTSS/TA higher than the ES plants while the fruits produced by RAI plants had lower weight and volume. However, the best quality for consumption (> TSS/TA and > weight) was achieved in Gr5stadium for the fruits of IRR plants and Gr6stadium for the fruits of RAI plants. These results indicated aphotoinhibition in WS plants influencingthe fruit quality, which presented fruit with greater accumulation of TSS and higherTSS/TA . Otherwise, e the water availability by irrigation has not affected the quality of the fruit at the end of the storage period